Intervenciones de enfermería en pacientes con insuficiencia renal aguda: revisión sistemática - Yungan Guamán, María Carmen (2025)
Introduction: This research analyzes the problem of acute renal failure from the perspective of nursing professionals’ processes. Objective: To describe nursing interventions in patients with acute renal failure through a systematic review. Methodology: A qualitative, descriptive research was conducted through a systematic review of scientific publications in databases such as Scielo, Elsevier, Dialnet, and Redalyc, including all articles published between 2021 and 2024 in Spanish, English, and Portuguese. The PRISMA methodology was structured, and 20 articles were selected. Results: The main risk factors for acute renal failure are hypertension, diabetes, and pyelonephritis, as well as the age group over 50 years. Complications are mainly associated with fluid retention, which can lead to pericardial inflammation and lung damage, resulting in renal loss that exposes the patient to dialysis. Therefore, the main interventions focused on assessing functional patterns, with special interest in hydration, nutrition, elimination, perception, and social conditions of patients with acute renal failure. Based on the nursing diagnosis, interventions for fluid, nutritional, and electrolyte balance were planned through parenteral feeding, catheterizations, antibiotic therapy, monitoring of vital signs, mechanical ventilation management, and nursing counseling. Conclusion: In conclusion, optimizing nursing interventions is an essential tool to improve patients' quality of life suffering from ARF.